Study on Thermal Stress of Honeycomb Ceramic Regenerators with Different Parameters - Wang, Y.X.; Dong, M.; Li, H.Y.; Liu, Y.Q.; Shang, Q.H. (Проблемы прочности, 2014)
In thermal flow-reversal reactor operations, honeycomb
ceramic regenerators are exposed to
thermal shock load. In this study, numerical simulations
of the temperature and thermal stress
distributions of honeycomb ceramic regenerators
are carried out using the CFX software.
Temperature variations with time are calculated
first for honeycomb ceramic regenerators with
holes of different shapes. Then, thermal stress
distributions of regenerators are analyzed with
different structural and operational parameters.
The analyses show that the thermal stress of honeycomb
ceramic regenerator depends on the
shape of holes, porosity and wall thicknesses.
This study provides a theoretical basis for optimization
of honeycomb ceramic regenerators. При работе ядерного реверс-поточного реактора керамические сотовые регенераторы подвергаются действию термоударной нагрузки. С помощью программного обеспечения CFX
проведено численное моделирование эпюр температуры и температурного напряжения керамических сотовых регенераторов. Исследовано изменение температур во времени для керамических сотовых регенераторов с отверстиями различной формы. Проанализированы
эпюры температурного напряжения регенераторов с разными конструкционными и эксплуатационными параметрами. Установлено, что температурное напряжение керамического
сотового регенератора зависит от формы отверстий, пористости и толщины стенок.
Результаты данного исследования служат теоретической базой для оптимизации керамических сотовых регенераторов. При роботі ядерного реверс-потокового реактора керамічні стільникові регенератори
зазнають дії термоударного навантаження. За допомогою програмного забезпечення
СFX проведено чисельне моделювання епюр температури і температурного напруження керамічних стільникових регенераторів. Досліджено зміну температур у часі
для керамічних стільникових регенераторів з отворами різної форми. Проаналізовано епюри температурного напруження регенераторів із різними конструкційними експлуатаційними параметрами. Установлено, що температурне напруження керамічного стільникового регенератора залежить від форми отвору, пористості і товщини стінок. Результати даного дослідження є теоретичною базою для оптимізації
керамічних стільникових регенераторів.